ENHANCING MUSICAL KNOWLEDGE IN STUDENT CLASSROOMS USING DIGITAL LEARNING RESOURCES - Jalilov Shokir Isomiddinovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the role of digital learning resources in reinforcing students’ musical knowledge within classroom settings. It explorespedagogical strategies, interactive tools, and multimedia applications that enhance comprehension, engagement, and practical application of theoretical concepts. The paper highlights the integration of digital platforms, simulations, and audio-visual resources to create immersive learning experiences. The effectiveness of these resources in improving musical literacy, auditory skills, and creative thinking is also discussed.